The Agony of The Slaves as Described in Frances Ellen Watkins Harper’s The Slave Auction - Christina Resnitriwati (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Black people were treated badly and cruelty by white people since the first time they were brought to America in between 1619 – 1865. In America most of them worked in huge plantation as slaves. Black people were considered as the second class citizens, and under the system of slavery. White people had the right to own, to buy and to sell them. The purpose of this paper is describe the sad and bitter experiences from the slaves when they were selling through the auction. The writer used tone and the historical background theories to understand the deep meaning of the poem and to feel the painful of the slaves’ conditions, as reflected in Harper’s The Slave Auction. The results from the discussion show us the really terrible condition of the slave when the auction was going on, and hopefully that the cruel thing done by people to other people will not be occurred any longer now and ever after.